High-flow warm humidified oxygen versus standard low-flow nasal cannula oxygen for moderate bronchiolitis (HFWHO RCT): an open, phase 4, randomised controlled trial. Issue 10072 (4th March 2017) - Kepreotes, Elizabeth; Whitehead, Bruce; Attia, John; Oldmeadow, Christopher; Collison, Adam; Searles, Andrew; Goddard, Bernadette; Hilton, Jodi; Lee, Mark; Mattes, Joerg
Summary: Background: Bronchiolitis is the most common lung infection in infants and treatment focuses on management of respiratory distress and hypoxia. High-flow warm humidified oxygen (HFWHO) is increasingly used, but has not been rigorously studied in randomised trials. We aimed to examine whether HFWHO provided enhanced respiratory support, thereby shortening time to weaning off oxygen. Methods: In this open, phase 4, randomised controlled trial, we recruited children aged less than 24 months with moderate bronchiolitis attending the emergency department of the John Hunter Hospital or the medical unit of the John Hunter Children's Hospital in New South Wales, Australia. Patients were randomly allocated (1:1) via opaque sealed envelopes to HFWHO (maximum flow of 1 L/kg per min to a limit of 20 L/min using 1:1 air–oxygen ratio, resulting in a maximum FiO2 of 0·6) or standard therapy (cold wall oxygen 100% via infant nasal cannulae at low flow to a maximum of 2 L/min) using a block size of four and stratifying for gestational age at birth. The primary outcome was time from randomisation to last use of oxygen therapy. All randomised children were included in the primary and secondary safety analyses. This trial is registered with the Australian New Zealand Clinical Trials Registry, number ACTRN12612000685819. Findings: From July 16, 2012, to May 1, 2015, we randomly assigned 202 children to either HFWHO (101 children) or standard therapy (101 children). Median time to weaning was 24 h (95% CI 18–28) for standard therapy and 20 h (95% CI 17–34) for HFWHO (hazard ratio [HR] for difference in survival distributions 0·9 [95% CI 0·7–1·2]; log rank p=0·61). Fewer children experienced treatment failure on HFWHO (14 [14%]) compared with standard therapy (33 [33%]; p=0·0016); of these children, those on HFWHO were supported for longer than were those on standard therapy before treatment failure (HR 0·3; 95% CI 0·2–0·6; p<0·0001). 20 (61%) of 33 children who experienced treatment failure on standard therapy were rescued with HFWHO. 12 (12%) of children on standard therapy required transfer to the intensive care unit compared with 14 (14%) of those on HFWHO (difference −1%; 95% CI −7 to 16; p=0·41). Four adverse events occurred (oxygen desaturation and condensation inhalation in the HFWHO group, and two incidences of oxygen tubing disconnection in the standard therapy group); none resulted in withdrawal from the trial. No oxygen-related serious adverse events occurred. Secondary effectiveness outcomes are reported in the Results section. Interpretation: HFWHO did not significantly reduce time on oxygen compared with standard therapy, suggesting that early use of HFWHO does not modify the underlying disease process in moderately severe bronchiolitis. HFWHO might have a role as a rescue therapy to reduce the proportion of children requiring high-cost intensive care. Funding: Hunter Children's Research Foundation, John Hunter Hospital Charitable Trust, and the University of Newcastle Priority Research Centre GrowUpWell.